A conceptual family partnership model with Paud institutions in developing the potential of early children based on blended learning - Lili Dasa Putr; Muhammad Fahrur Rozi; Ciptro Handrianto; M Arinal Rahman (Ensaio)
This article aimed to provide a conceptual model of a family partnership with Paud institutions to develop the potential of young children based on blended learning. The approach was broken down into three stages: first, determining the learning needs of the parents in connection to the expansion of their competence in training; second, determining the learning needs of each mentor via the use of a learning needs identification format and questionnaire; and third, supplementing interviews. After that, the model’s effectiveness was evaluated by organizing offline and online collaboration activities using various technology, information, and communication forms. The empirical findings and input on the conceptual model, which had previously been evaluated for viability, were used to create the model after the trial done by professionals, practitioners, and students on the efficacy of blended learning for mentor training. The trial results were utilized to construct the model, following the empirical findings and input.